“Nós não somos agência humanitária, nós somos a agência do Reino de Deus”: proselitismo religioso e ação social evangélica com migrantes - Faustino, Rafael (Universidade Federal de São Carlos, 2026)
In this research, I investigate the extent to which the assistance provided by evangelical organizations and churches to people in forced displacement is conditioned by an expectation of religious loyalty or adherence. To this end, I analyze the activities of a network of evangelical churches in relation to Ukrainians brought to Brazil following the onset of the war in Ukraine in 2022. Data collection was conducted through 22 semi-structured interviews carried out during fieldwork in Curitiba and Prudentópolis, in the Brazilian state of Paraná, with representatives of participating churches, volunteers and other individuals involved in the migration process, and Ukrainian migrants who remained in the country. Data analysis is guided by the Sociological Discourse Analysis (SDA) developed by the Madrid Qualitative School, understanding discourse not merely as vocabulary employed, but as a form of production of reality and knowledge, inscribed in power dynamics and beyond intentionality. I argue that evangelical churches and organizations frequently operate in the migration field in a proselytizing manner and with expansionist objectives, utilizing social actions to fulfill the biblically inspired mission of converting people from all nations. These actors pursue this end through diverse approaches and discourses but often seek an "integral" action that positions them as the primary or sole benefactors of the assisted individuals, while discouraging them from seeking other sources of support. These strategies encounter barriers that limit their outcomes, the main one being the difficulty of reaching a significant number of non-evangelicals in specific contexts. I further suggest that there is a trend toward growth in evangelical social action regarding forced displacement, stemming from religious leaders' identification of this field as fertile for reaching individuals of diverse cultural and religious profiles; from their extensive networks of religious, political, and economic connections; and from the increasing openness of national states and international organizations to their participation in humanitarian policies and in the migration governance.
“We are not a humanitarian agency, we are the agency of the Kingdom of God”: religious proselytism and evangelical social action with migrants
Keywords: Igrejas evangélicas; Deslocamento forçado; Organizações religiosas; Governança migratória; Proselitismo religioso; Ação social evangélica; Forced displacement; Faith-based organizations; Migration governance; Evangelical social engagement; Religious proselytism; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS; 10. Redução das Desigualdades; 17. Parcerias e Meios de Implementação; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável